Little Turkey in the Medan Maimun Area - Ginting, Nurlisa; Zahrah, Wahyuni; Nasution, Achmad Delianur; Sitorus, Muhammad Aria; Shafira Imanina; Ervina Lestari; Shayra Anastsasya Shafwani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service is one of the core activities of the Tri Dharma of Higher Education. This activity is carried out as an effort to apply practical scientific knowledge to comprehensively address community problems in the field by involving both the community and university lecturers collaboratively. The current community service activity focuses on urban spatial planning issues in the Jl. Mahkamah area, Medan Kota District, Medan City, North Sumatra. The theme of this project is "Little Turkey," which is related to the Al-Mashun Mosque by proposing urban space designs and building facades along Jl. Mahkamah. The implementation of this community service follows a series of stages, starting with field surveys, conducting the first and second meetings, and finally delivering the final design to the local government and community. The outcome of this community service is expected to serve as an initial step toward further developing and enhancing the architectural quality of Medan City and improving the local community’s economy.